2022
DOI: 10.3390/vaccines10071099
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Science as a Possible Mediator between Different Antecedents and COVID-19 Booster Vaccination Intention: An Integration of Health Belief Model (HBM) and Theory of Planned Behavior (TPB)

Abstract: As the literature highlights, many health behavior theories try to explain both social and psychological variables influencing an individual’s health behavior. This study integrates insights relative to the antecedents of getting vaccinated from health behavior theories, particularly including the health belief model (HBM), the theory of planned behavior (TPB), and the different socio-demographic factors. Furthermore, we considered the possible mechanism of impact of distrust in science on individuals’ hesitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 134 publications
5
24
0
Order By: Relevance
“…The ‘progress’ theme emerged from 6% of answers related to trust in scientific research and science (e.g., ‘evolution’). Interestingly, all individuals included in this category were vaccinated against COVID-19, confirming the results by Barattucci and colleagues (2012) [ 36 ]. Thus, the authors have shown that trust in science plays a crucial role in predicting vaccination intention, mediating the relationship between individual factors (i.e., fear of COVID-19, and subjective norms) and vaccination intention [ 36 ].…”
Section: Discussionsupporting
confidence: 87%
“…The ‘progress’ theme emerged from 6% of answers related to trust in scientific research and science (e.g., ‘evolution’). Interestingly, all individuals included in this category were vaccinated against COVID-19, confirming the results by Barattucci and colleagues (2012) [ 36 ]. Thus, the authors have shown that trust in science plays a crucial role in predicting vaccination intention, mediating the relationship between individual factors (i.e., fear of COVID-19, and subjective norms) and vaccination intention [ 36 ].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, meticulous calculations may take time, delaying vaccine uptake. Clear, sound (e.g., coherent, and not contradictory), concise, and honest vaccine-related communications may favor solid knowledge and quick, efficient decisions; also, this manner of communicating may favor individuals’ trust in science, which has been recently reported to be a crucial mediator of COVID-19 vaccine acceptance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…to PCO (H10), leading us to believe that personal 839 studies to investigate the impact of health beliefs 840 on older adults' reasoned actions [77,83]. The…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%